Analysis of Teacher's Capability in Implementing Limited Face to Face Learning Evaluation At SDN 106790 Sei Mencirim Deli Serdang - Tisa Enika Sitepu (Lembaga Riset Ilmiah, 2022)
This study aims to analyze the ability of teachers in the implementation of limited face-to-face learning evaluation at SDN 106790 Sei Mencirim. With the research subject, the teachers of SDN 106790 Sei Mencirim. This study uses a quantitative approach. With the number of teachers as respondents as many as 12 people. The determination of the school sample was carried out randomly and purposively. The number of respondents is 12 people who have varying ages and lengths of teaching. Data collection was carried out by filling out questionnaires conducted by respondents and interviews. The results obtained are that only 15% of teachers can carry out learning evaluations by combining evaluation with online learning and face-to-face evaluation as a solution for implementing learning evaluations during the limited face-to-face learning period so that sufficient training is needed for teachers so that they can improve the ability of teachers in the implementation of limited face-to-face learning evaluations.